Ethical Implications of Public Relations in Bangladesh: Islamic Perspective - Haque, Md. Shariful; Shahnewaz, Syeda Tanjila; Siddikee, Md. Noman (Asian Business Review, 2013)
This paper aims to examine public relation practices in Bangladesh, weighing its ethical implications from an Islamic perspective and investigates whether it comply with Islam’s ethical specifications to facilitate Muslim Marketer’s thoughts and practices. The paper uses Qur’an (Chapter 3, Verse 103) as a theoretical framework to critically evaluate relevant information to ascertain the extent of ethical legitimacy of promotional strategies used in public relations in Bangladesh. It cites relevant references from Qur’an and Sunnãh as interpretive evidences and methodology. Islam puts stress on institutionalizing ethics in every aspects of Business. This complete code of life strongly recommends Muslims to do business which should certainly be in the ethical framework guided by Shari’ah. The existing public relation strategies in Bangladesh are ethically dubious. Undue influence, exertion of too much political power, flattering, fabrication, falsehood, and bribery are very much common practices done by the corporations to build favorable public relations. No ways are these in compliance with Islamic Ethical Values. This paper suggests the necessity for further research into the ethical dimensions of business practices in Bangladesh to promote ethical awareness in the society. This study includes mutual socio-economic and ethical responsibilities among Bangladeshi Marketers to save the society from corruption and moral deterioration. JEL Classification Code: M10, M30